Measuring Empathy among Dental Students and Interns: A Cross-Sectional Study from Dammam, Saudi Arabia. (27th April 2021) - Nazir, Muhammad; Alhareky, Muhanad; Alqahtani, Abdulrahman; Alsulaimi, Leenah; Alotaibi, Reema; Yousef, Najwa; Abushal, Fatimah; Alhumaid, Jehan
Abstract : Objective . To evaluate empathy and its related factors among undergraduate dental students and interns enrolled in a public dental college in Dammam, Saudi Arabia. Materials and Methods . This cross-sectional study used the Jefferson Scale of Empathy-Health Profession Students (JSE-HPS) version to determine empathy in 362 dental students and interns in Dammam, Saudi Arabia. The JSE-HPS is a 20-item 7-point Likert scale questionnaire, and its score ranges from 20 to 140 with high values indicating increased empathy. Influences of age, gender, class year, previous year's grade point average (GPA), educational attainment of parents, and monthly family income on empathy were evaluated. Results . Of 501 enrolled students and interns, 362 returned completed questionnaires, and the response rate of the study was 72%. The sample's empathy score (JSPE-HPS scale) ranged from 70 to 129 with a mean of 96.75 (±13.76). Most participants believed that empathy is important for effective communication with patients (96.1%) and can improve the provider-patient relationship (95.6%). Females demonstrated a significantly higher mean empathy score (99.98 ± 14.01) than males (92.72 ± 12.35) (P < 0.001 ). Similarly, the participants with high GPA (98.06 ± 13.69) had significantly greater mean empathy scores than those with low GPA (94.84 ± 13.68) (P = 0.029 ). The mean empathy score increased significantly from junior students (3 rd and 4 th year students) to senior students (5 th and 6 th year students) and interns (P = 0.008 ). Multiple linear regression analysis showed that class year ( B = 2.03, P = 0.006 ) and GPA ( B = 8.67, P = 0.003 ) were significant factors associated with empathy. Conclusions . Empathy is important for effective patient communication and improved provider-patient relationship. Female gender, high GPA, and class years were associated with empathy. Empathy should be integrated into dental curricula for effective student learning and positive patient care outcomes.